SAT0449 Progression from undifferentiated spondyloarthritis to ankylosing spondylitis: Is USPA a proxy for non-radiographic axial SPA?. (23rd January 2014) - Boonen, A.; Kirson, N.Y.; Rao, S.A.; Birnbaum, H.G.; Swallow, E.; Yushkina, Y.; Jarvis, J.; Mease, P.J.; Cifaldi, M.A.
Abstract : Background: Axial spondyloarthritis (axSpA) is a new umbrella term including patients with ankylosing spondylitis (AS), as well as those with non-radiographic axSpA (nr-axSpA). The new classification provides accepted evidence-based criteria to diagnose these patients. However, in practice, patients may be diagnosed using an earlier disease concept—undifferentiated SpA (uSpA)—for which an ICD-9 code exists. While clinical studies have found that a proportion of nr-axSpA patients experience radiographic progression (ie, to AS), little is known about progression to AS in a real-world setting. Objectives: Explore the rate at which patients diagnosed with uSpA were subsequently diagnosed with AS using a large claims database. Methods: Patients were selected from a de-identified US private insurer claims database (2000–2010). Potential nr-axSpA patients were defined as patients with ≥1 diagnosis for uSpA (ICD-9: 720.9) and a history of back disorders (724.0-724.9) prior to uSpA diagnosis. The date of first uSpA diagnosis was used as the study index date. Patients were required to have ≥6 months of continuous enrollment in a health plan prior to index (baseline period); be ≥18 years old on index; have no diagnoses for rheumatoid arthritis (714.0) or any type of SpA (AS: 720.0; Psoriatic Arthritis: 696.0; Reactive Arthritis: 099.3, 711.1; Inflammatory Bowel Disease: 713.1) on or before index; and have no diagnoses for any type of SpA other than AS post-index. Patients were followed until the earliest of: (a) diagnosis of AS (progression); (b) end of continuous eligibility; or (c) end of data availability. Baseline characteristics were measured separately for patients who were subsequently diagnosed with AS, and compared with those with no diagnosed progression. Results: 6045 patients met the sample selection criteria. Median (IQR) available follow up was 14.2 (5.8-29) months. Two years post index, 8.9% of patients were diagnosed with AS, increasing to 13.7% by the 7 year mark. 5590 patients had no subsequent AS diagnosis. These patients averaged 47.6 years of age, and 61.4% were female. In comparison, patients progressing to AS were younger (43.8 years, P <.001), and 54.1% were female ( P =.002). AS progressors also had higher baseline rates of uveitis (8.4% vs. 1.5%, P <.001) and were more likely to use NSAIDs (46.4% vs. 36%, P <.001) and DMARDs (14.3% vs. 6.2%, P <.001) at baseline. Conclusions: In a database study of real-world diagnostic patterns, approximately 14% of patients diagnosed with uSpA and with a history of back disorders progressed to AS over a 7 year period. Patients progressing to AS were younger and more likely to have a history of uveitis. To the extent that the combination of these ICD-9 codes serves as a proxy for nr-axSpA, the observed progression rates are on the lower end of previously reported findings in clinical studies. Disclosure of Interest: A. Boonen: None Declared, N. Kirson Consultant for: Under contract with Abbott, Employee of: Analysis Group, S. Rao Shareholder of: Abbott, Employee of: Abbott, H. Birnbaum Consultant for: Under contract with Abbott, Employee of: Analysis Group, E. Swallow Consultant for: Under contract with Abbott, Employee of: Analysis Group, Y. Yushkina Consultant for: Under contract with Abbott, Employee of: Analysis Group, J. Jarvis Consultant for: Under contract with Abbott, Employee of: Analysis Group, P. Mease Consultant for: Abbott, M. Cifaldi Shareholder of: Abbott, Employee of: Abbott